CHOMSKY'S SUB-THEORIES IN PRINCIPLES AND MEDIA: PRESENTATION AND STUDY - Maryam Fadhil Neamah; Hadeel Abdulameer Hassooni; Suad Jubair Sulta (American Journals Publishing, 2024)
This Research Deals with Chomsky's Sub-Theories in The Third Stage of The Generative Theory, Which Is the Stage of Principles and Mediators or The Stage of Work and Connection. The Aim of This Research Is Not to Promote a Doctrine or A Specific Linguistic Theory, But Rather to Attempt to Define the Theory of Principles and Mediators and Study and Apply It to Our Arabic Language. This Theory First Appeared in Chomsky's Book Entitled (Lectures on Work and Connection) And Its Features Became Clear and Evident in His Book Linguistic Knowledge: Its Nature, Origins and Use. This Theory Was Described as The First Real Creative Approach to Language. This Theory Was Composed of Several Sub-Templates That Interacted With Each Other And with The Ideas That Entered It. These Templates (The Theory of The Parietal Sin, The Theory of The Axis, The Theory of The Limits, The Theory of The Case, The Theory of Work, The Theory of Connection). The Research Presented It After the Introduction That Included the Definition of This Theory and Then the Axes of The Theory Accompanied by Its Definitions and Applications to The Arabic Language. Then The Research Concluded with A Conclusion That Included the Most Important Results Reached by This Research. As For the Method Followed in Our Study, It is the Descriptive Analytical Method And It Included Some Applied Examples of These Theories.
Keywords: Principles And Media, Chomsky, Work And Connection.